Frequency of Hyponatremia in Patients with Chronic Kidney Disease in a Tertiary Care Hospital - Amin Anjum, Muhammad Afzal, Rashid Mahmood Khan, Atif Maqsood, Faizan Aslam, Nida, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To assess the frequency of hyponatremia in patients with chronic kidney disease. Materials and Methods: The design of this study was cross sectional study design. This study was conducted in the Department of Nephrology, in a DHQ Hospital Faisalabad. Totally 179 patients who were suffering from chronic kidney disease were enrolled. A 3ml blood samples were taken from each patient and sent for the measurement of electrolytes to the hospital laboratory. A unique number will be given to each sample. All the demographic details and study results were recorded on a predesigned data collection proforma. Results: Out of total 179 patients, 105 were male and 74 were female with mean age of 40.91±12.13 years. The most common age group was 20-35 years in which 76 (42.5%), followed by 36-50 years in which 52 (29.0%) and 51 (28.5%) patients were in the age group of < 60 years. 41.9%) patients have hyponatremia while 104 (58.1%) patients do not have hyponatremia. Frequency distribution of different variables in patients with respect to Hyponatremia was done ad it was noted that P-value was not significant. Practical Implication: In human Hyponatremia develops as a result of the kidney’s inability to emit extra water, particularly in chronic kidney disease (CKD). In CKD the human kidney fails to regulate water homeostasis. The main aim of this study was to determine the frequency of hyponatremia in CKD patients. Conclusion: It is concluded that in most of the CKD patients, hyponatremia was developed. And also, hyponatremia is age dependent so in elder patients the hyponatremia prone to develop. Keywords: Hyponatremia, Chronic Kidney Disease, Frequency, Laboratory, Variables, Symptom.